Borderline Personality Disorder With Depression Confers Significant Risk of Suicidal Behavior in Mood Disorder Patients—A Comparative Study - Söderholm, John J.; Socada, J. Lumikukka; Rosenström, Tom; Ekelund, Jesper; Isometsä, Erkki T. (Frontiers in Psychiatry, 2020)
Objective: We investigated risk factors for suicidal ideation and behavior among currently depressed patients with major depressive disorder (MDD), major depressive episode (MDE) in bipolar disorder (BD), or MDE with comorbid borderline personality disorder (MDE/BPD). We compared current and lifetime prevalence of suicidal ideation and behavior, and investigated dimensional measures of BPD or mixed affective features of the MDE as indicators of risk. Methods: Based on screening of 1655 referrals, we recruited 124 psychiatric secondary care outpatients with MDE and stratified them into three subcohorts (MDD, BD, and MDE/BPD) using the Structured Clinical Interview for DSM-IV I and II. We examined suicidal ideation and behavior with the Columbia Suicide Severity Rating Scale (CSSRS). In addition, we quantified the severity of BPD symptoms and BD mixed features both categorically/diagnostically and dimensionally (using instruments such as the Borderline Personality Disorder Severity Index) in two time frames. Results: There were highly significant differences between the lifetime prevalences of suicide attempts between the subcohorts, with attempts reported by 16% of the MDD, 30% of the BD and 60% of the BPD subcohort. Remarkably, the lifetime prevalence of suicide attempts in patients with comorbid BD and BPD exceeded 90%. The severity of BPD features was independently associated with risk of suicide attempts both lifetime and during the current MDE. It also associated in a dose-dependent manner with recent severity of ideation in both BPD and non-BPD patients. In multinominal logistic regression models, hopelessness was the most consistent independent risk factor for severe suicidal ideation in both time frames, whereas younger age and more severe BPD features were most consistently associated with suicide attempts. Conclusions: Among patients with major depressive episodes, diagnosis of bipolar disorder or presence of comorbid borderline personality features both imply remarkably high risk of suicide attempts. Risk factors for suicidal ideation and suicidal acts overlap, but may not be identical. The estimated severity of borderline personality features seems to associate with history of suicidal behavior and current severity of suicidal ideation in dose-dependent fashion among all mood disorder patients. Therefore, reliable assessment of borderline features may advance the evaluation of suicide risk.